The role of burnout in the effect of work-family conflicts on job satisfaction: A research for key players in the maritime industry - Turan, Eda; Bozkurt, Serdar; Celebi, Ugur Bugra; Ekinci, Serkan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Maritime is one of the sectors where conflicts from work to the family are experienced the most. It is vital to examine the results of behavioral outputs in an area where staying away from the family is so effective that burnout is accompanied by severe difficulty. The primary purpose of the study is to examine the role of burnout in the impact of work-family conflicts (WFC) experienced by key players in the maritime industry on job satisfaction. Data gathered from 372 participants working in the maritime sector were analyzed using structural equation modeling (SEM). The results show that burnout has a partial mediating effect on job satisfaction. After the literature review and results, the applications that motivate and keep key players engaged are discussed. In this context, for those working in the maritime industry, from work to family conflict has been shown to play a critical role in burnout and job satisfaction modeling.
Keywords: Work-family conflict; job satisfaction; burnout; structural equation modeling; maritime industry; TURNOVER INTENTION; SEAFARERS; BEHAVIOR; STRESS; Transportation